Dengue fever and pregnancy - Purizaca Benites, Manuel (2015)
We present the impact of dengue fever epidemic on people as well as its transmission, pathogenia, symptomatology and treatment. We explain the risks of an exposed pregnant woman to dengue fever since the possibility of complications increase. We consider the need of effective public policies in the possibility of an epidemic.